Achieving Diagnosis by Consensus - KANE, BRIDGET; LUZ, SATURNINO (My University, 2009)
This paper provides an analysis of the collaborative work conducted at a multidisciplinary medical team meeting, where a patient's definitive diagnosis is agreed, by consensus. The features that distinguish this process of diagnostic work by consensus are examined in depth. The current use of technology to support this collaborative activity is described, and experienced deficiencies are identified. Emphasis is placed on the visual and perceptual difficulty for individual specialities in making interpretations, and on how, through collaboration in discussion, definitive diagnosis is actually achieved. The challenge for providing adequate support for the multidisciplinary team at their meeting is outlined, given the multifaceted nature of the setting, i.e. patient management, educational, organizational and social functions, that need to be satisfied.
PUBLISHED
Keywords: COLLABORATIVE COMPUTING; multidisciplinary medical team; Smart & Sustainable Planet